Contribution of MUTYH Variants to Male Breast Cancer Risk: Results From a Multicenter Study in Italy - Rizzolo, Piera; Silvestri, Valentina; Bucalo, Agostino; Zelli, Veronica; Valentini, Virginia; Catucci, Irene; Zanna, Ines; Masala, Giovanna; Bianchi, Simonetta; Spinelli, Alessandro Mauro; Tommasi, Stefania; Tibiletti, Maria Grazia; et al. (Frontiers in Oncology, 2018)
Inherited mutations in BRCA1, and, mainly, BRCA2 genes are associated with increased risk of male breast cancer (MBC). Mutations in PALB2 and CHEK2 genes may also increase MBC risk. Overall, these genes are functionally linked to DNA repair pathways, highlighting the central role of genome maintenance in MBC genetic predisposition. MUTYH is a DNA repair gene whose biallelic germline variants cause MUTYH-associated polyposis (MAP) syndrome. Monoallelic MUTYH variants have been reported in families with both colorectal and breast cancer and there is some evidence on increased breast cancer risk in women with monoallelic variants. In this study, we aimed to investigate whether MUTYH germline variants may contribute to MBC susceptibility. To this aim, we screened the entire coding region of MUTYH in 503 BRCA1/2 mutation negative MBC cases by multigene panel analysis. Moreover, we genotyped selected variants, including p.Tyr179Cys, p.Gly396Asp, p.Arg245His, p.Gly264Trpfs*7 and p.Gln338His, in a total of 560 MBC cases and 1540 male controls. Biallelic MUTYH pathogenic variants (p.Tyr179Cys/p.Arg241Trp) were identified in one MBC patient with phenotypic manifestation of adenomatous polyposis. Monoallelic pathogenic variants were identified in 14 (2.5%) MBC patients, in particular, p.Tyr179Cys was detected in seven cases, p.Gly396Asp in 5 cases, p.Arg245His and p.Gly264Trpfs*7 in 1 case each. The majority of MBC cases with MUTYH pathogenic variants had family history of cancer including breast, colorectal and gastric cancers. In the case-control study, an association between the variant p.Tyr179Cys and increased MBC risk emerged by multivariate analysis [odds ratio (OR)=4.54; 95% confidence interval (CI): 1.17-17.58; p=0.028]. Overall, our study suggests that MUTYH pathogenic variants may have a role in MBC and, in particular, the p.Tyr179Cys variant may be a low/moderate penetrance risk allele for MBC. Moreover, our results suggest that MBC may be part of the tumor spectrum associated with MAP syndrome, with implication in the clinical management of patients and their relatives. Large-scale collaborative studies are needed to validate these findings.